Analysis of Workload and Work Environment on Reducing Medication Errors with the Use of Technology as an Intervening Variable in Inpatient Pharmacy Depots Bogor City Regional Hospital - Pitri Sukmaning Rahayu; Ratnawati Prayogi; Jones Zenas Rante; Rudianto Rudianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to analyze the impact of workload and work environment on reducing medication error through the use of technology as an intervening variable in the Inpatient Pharmacy Depot of RSUD Kota Bogor. Medication error refers to errors in the medication process that can endanger patients, and this research examines how workload, work environment, and technology influence such errors. The research method employed is quantitative, using a survey approach with questionnaires distributed to 30 pharmaceutical staff at the Inpatient Pharmacy Depot of RSUD Kota Bogor. Data analysis was conducted using the Partial Least Square (PLS) method. The results show that workload has a significant effect on medication error. The higher the workload, the greater the risk of medication errors. However, workload does not have a significant impact on the use of technology. On the other hand, the work environment does not significantly affect medication error, but it does have a significant influence on the use of technology. Technology, in turn, does not significantly reduce medication error and does not mediate the relationship between workload or work environment and medication error.Based on these findings, it is recommended that the management of RSUD Kota Bogor improves workload management and optimizes the use of technology by providing better training to pharmaceutical staff. Additionally, efforts should be made to enhance the work environment to better support the implementation of technology in reducing medication errors and improving patient safety.